Experimental investigation and validation of structural properties of a new design for active twist rotor blades - Kalow; S.; Kamp, B. van de; Keimer, R.; Riemenschneider, J. (My University, 2017)
Vibration and noise are omnipresent in a helicopter environment and therefore their reduction is an important goal in helicopter research. Actuators embedded into the skin of a helicopter rotor blade can produce a twist, which influences the propagation of the air turbulence. Hence, vibration and noise levels can be significantly reduced. An important issue during operation of a rotor blade are the centrifugal loads which affect the actuators and can cause failure. Based on the German Aerospace Center (DLR) project STAR, the design of an active twist rotor blade has been adapted, such that the loads in the actuator system can be significantly reduced and furthermore distributed evenly. Besides a new actuator design, decribed in an earlier study of the authors, this paper focus on the use of carbon fiber composite for the spar and additional straps near to the trailing edge. This increases the durability of a new generation of active twist rotor blades, which is the basis for a specific and efficient use of the active twist technology. A first prototype of the new designed rotor blade has already been built. The design changes are addressed in this paper as well as parts of the manufacturing process. Also results of the numerical model are validated experimentally and blade properties of the prototype blade are presented.